PENGARUH PENAMBAHAN CMC SEBAGAI SENYAWA PENSTABIL TERHADAP YOGHURT TEPUNG GEMBILI - Dewi Cakrawati; Mochamad Angga Kusumah (AGROINTEK, 2016)
The study aims to determine the effect of CMC in preventing yoghurt separation in 7 days with the addition of 2% Dioscorea esculenta flour. Organoleptic test using quality hedonic was conducting to find out yoghurt with addition of CMC that had accepted characteristic by panelists. Research was carried out using regression method to determine the total titrated acid, pH and separation level of yoghurt during storage. The concentrations of CMC were added at 0.2%, 0.4%, 0.6%, 0.8%. The analysis showed the addition of 0.6% CMC showed the lowest separation with high viscosity grades of DPAs 40.25. Yoghurt storage for 7 days shows a graph of the pH value and total titrated acid were parabolic where increasing in total titrated acid value would lower the pH value. Yoghurt was damaged on the 7th day of storage at room temperature characterized by the increasing in the pH value and damage to the organoleptics properties, namely yoghurt flavor and aroma.